KOMPETISI ANTAR MODA PADA ANGKUTAN PETI KEMAS BANDUNG -JAKARTA - Widiastuti, Ratna
Abstract: Bandung metropolitan, which is situated in an hinterland, is a production center of export commodity. The volume of export commodity that transported in containers to Tanjung Priok Harbor by train and highway trucks is increasing. In the near future the competition scheme between both transportation modes will change due to the upcoming existence of the Padalarang-Cikampek Toll Road and the dispatch priority of the container train that will be set up higher. The objectives of this study are to identify dominant variables affecting the competition of both transportation modes in getting their respective share in transporting containers, to identify the competition behavior by means of a Binary Logit Model, and to anticipate the change of each mode\'s competitiveness. A survey oh 40% of the container transportation users of the Bandung to Jakarta route is conducted to identify the relative importance of modal split variables and to estimate the parameters of the Binary Logit Model. A Pseudo-linear multiregression is used in the estimation. The estimation results are cross-checked statistically with preference identified in the survey. The study also identifies a competition scenario which is used with the model to predict the share change of each transportation mode. It is concluded directly from the survey of preference that the most dominant variable determining the share of each mode is transportation time followed by the variables of transportation costs and the time needed for completing paperwork. A Binary Logit Model with a determination coefficient of 81% is accounted with the three variables. There is a consistency between the relative importance of variables derived from the model and that of the survey of preference. It is anticipated that there will be a new scheme of competition characterized by 3 hour shorter (30% faster) of train transportation with the cost increase of Rp 100 thausand (2% higher) and 1.25 hour shorter (12% fsdter) of truck transportation with the cost increase of Rp 13.5 dhousand. As a result, the share of train in transporting containers will change from 47% to 76%, whilst the share of the truck will change from 53% to 24%.